Pengaruh Review Barang dan Kemudahan Bertransaksi Terhadap Minat Beli Mahasiswa Prodi Pendidikan Ekonomi pada Platform TikTok Shop - gale, adelfina; Titik Purwati; Novi Eko Prasetyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The objective of this research is to understand and analyze the simultaneous and individual effects of product reviews and transaction convenience on the purchase intention of economics education students on the TikTok shop platform. This study used quantitative data from questionnaires distributed to 110 respondents. The result of the t – test found that both product reviews and transaction convenience positively influence purchase intention. Furthermore, the f – test result indicated that product reviews and transaction convenience simultaneously affect purchase intention.